096 Effects of Rotating Antibiotic and Ionophore Feed Additives on Enteric Methane, Volatile Fatty Acid Production and Rumen Microbial Populations of Steers Consuming a High Forage Diet. (1st February 2016) - Crossland, W. L.
Abstract: Ionophore and antibiotic feed additives have been shown to decrease ruminal methanogenesis, but evidence of long-term mitigation is lacking. We proposed a rotation of feed additives as an alternative to reduce methane (CH4 ) production. Rumen-cannulated steers (n = 12) were fed a basal high forage diet at 2% of BW (DM) for 13 wk in a Calan gate facility receiving 1 of 6 treatments (trt): 1) control (Con) no additive, 2) bambermycin (B) = 20 mg B/hd/d, 3) monensin (M) = 200 mg M/hd/d, 4) B7M= rotating B and M treatments weekly, 5) B14M = rotating B and M treatments every 14 d, and 6) B21M= rotating B and M treatments every 21 d. Steers were blocked by weight in a RCBD with repeated measures. Rumen fluid was collected weekly for in vitro analysis (n = 13) and results were normalized according to organic matter intake (kg OMI). Trt tended to affect CH4 to Propionate ratio (CH4 :Pro) ( P = 0.06) being highest in Con and lowest in M, B21M, and B14M (0.42 vs. 0.36, 0.36, and 0.33, respectively). CH4 :Pro was lower for wks 2 and 3 ( P < 0.05) than other weeks. Week also affected total VFA peaking at wk 3 and plummeting wk 4 (4.02 vs 2.86 mM/kg OMI; P < 0.05). Trt affected gram positive (G + ) bacteria populations being greater for rotationally fed steers than continuously fed steers and Con ( P < 0.01) and revealing wk 0 was different from wk 5 and 6 but was similar to wk 12 (51.1 vs. 37.5 and 35.1 vs. 44 %, respectively; P < 0.01). Interestingly, one class of G - bacteria ( Sphingobacteriia ), phylum Bacteroidetes, was not affected by trt or wk but was positively correlated with CH4 production (r = 0.24, P = 0.04) and tended to be a significant covariate to model CH4 production ( P = 0.09). Methanobrevibacter spp. population tended to correlate with CH4 production (r = 0.22, P = 0.07) and was affected by trt where populations in M were greater than B14M (68.9 vs. 51.0 % of Archaea; P < 0.01). Wk 0 populations tended to be greater than wk 3 but were not different from wk 12 (60.6 vs. 53.6 vs. 66.3 % of Archaea; P = 0.09). Our results suggest microbial adaptation to each trt at some degree. Further investigation of statistical tendencies are merited within phylum of interest.